LEGAL PROTECTION FOR VICTIMS OF CHILD TRAFFICKING - Thamrin, Angelia Regita; Astutik, Sri; Subekti, Subekti; Yuwono, Stevanus Budi; Yuwono, Stevanus Budi (Proceeding of International Conference on Multidisciplinary Research, 2024)
Children are the next generation and determine the future of the nation as well as a mirror of the attitude of life in the future, so children need to get the opportunity to grow and develop optimally, both physically, mentally and socially. But in this case, sometimes children also experience problems, namely becoming victims of child trafficking committed by their biological mothers, which has been prohibited in the provisions of Article 76f junto Article 83 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The sale of children is one form of crime that violates human rights, whose perpetrators are not only other people but also their biological mothers. Where children are vulnerable to becoming victims of the criminal act of selling children because children are easy to deceive, instigate, or lure because children's thinking is still not as mature as adults. So it needs to be taken seriously and provide special protection to children as victims of the crime of selling children.